Comparative Genetic Diversity of Pseudomonas stutzeri Genomovars, Clonal Structure, and Phylogeny of the Species - Cladera, Aina Maria (American Society for Microbiology, 2004)
A combined phylogenetic and multilocus DNA sequence analysis of 26 Pseudomonas stutzeri strains distributed within the 9 genomovars of the species has been performed. Type strains of the two most closely related species (P. balearica, former genomovar 6, and P. mendocina), together with P. aeruginosa, as the type species of the genus, have been included in the study. The extremely high genetic diversity and the clonal structure of the species were confirmed by the sequence analysis. Clustering of strains in the consensus phylogeny inferred from the analysis of seven nucleotide sequences (16S ribosomal DNA, internally transcribed spacer region 1, gyrB, rpoD, nosZ, catA, and nahH) confirmed the monophyletic origin of the genomovars within the Pseudomonas branch and is in good agreement with earlier DNA-DNA similarity analysis, indicating that the selected genes are representative of the whole genome in members of the species.